Odpowiedź :
Odpowiedź:
[tex]l)\ \ \sqrt{20}=\sqrt{4\cdot5}=\sqrt{4}\cdot\sqrt{5}=2\sqrt{5}\\\\l)\ \ \sqrt[3]{16}-\sqrt[3]{2}=\sqrt[3]{8\cdot2}-\sqrt[3]{2}=2\sqrt[3]{2}-\sqrt[3]{2}=\sqrt[3]{2}\\\\m)\ \ \sqrt[3]{125}-\sqrt[3]{8}=5-2=3\\\\n)\ \ \sqrt[3]{27}:\sqrt[3]{-8}=3:(-2)=-\frac{3}{2}=-1\frac{1}{2}\\\\o)\ \ \sqrt{2\sqrt{4}}=\sqrt{2\cdot2}=\sqrt{4}=2\\\\p)\ \ \sqrt[3]{9\cdot\sqrt[3]{27}}=\sqrt[3]{9\cdot3}=\sqrt[3]{27}=3 [/tex]
[tex]r)\ \ \sqrt[3]{\frac{1}{8}\cdot(-125)}=\sqrt[3]{-\frac{125}{8}}=-\frac{5}{2}=-2\frac{1}{2}\\\\s)\ \ (2\sqrt{3})^2=2^2\cdot(\sqrt{3})^2=4\cdot3=12\\\\t)\ \ (3\sqrt{2})^3=3^3\cdot(\sqrt{2})^3=27\cdot\sqrt{8}=27\cdot\sqrt{4\cdot2}=27\cdot2\sqrt{2}=54\sqrt{2} [/tex]